MIF is a 3’ flap nuclease that facilitates DNA replication and promotes tumor growth - Yijie Wang (Nature Portfolio, 2021)
Replication stress is associated with cancer formation and progression. Here the authors reveal that the macrophage migration inhibitory factor (MIF) functions as 3’ flap nuclease involved in resolving replication stress affecting overall tumor progression.